Animosity and religiosity in brand switching via boycott intention among muslim consumers - Fernanda, Redithya Ega; Handayanto, Eko; Fiandari, Yulist Rima (Asian Journal of Islamic Management (AJIM), 2025)
Purpose – This study analyzes the influence of animosity and religiosity on brand switching among Pizza Hut consumers in Indonesia, with boycott intention as a mediating variable. It seeks to understand how negative sentiments and religious values shape consumers’ decisions to switch brands in the context of geopolitical and social conflicts.Methodology – A quantitative approach was employed, utilizing a survey distributed to 190 Pizza Hut consumers in Indonesia. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) via SmartPLS 4.0 to test the direct and indirect effects among variables.Findings – The results confirmed that both animosity (β = 0.174, p < 0.05) and religiosity (β = 0.240, p < 0.05) significantly influenced brand switching. Boycott intention also mediated these relationships, with animosity (β = 0.126, p < 0.05) and religiosity (β = 0.149, p < 0.05) exerting indirect effects. Additionally, boycott intention directly affects brand switching (β = 0.402, p < 0.05).Implications – Practically, Pizza Hut must address consumer animosity rooted in political conflict and align marketing strategies with religious values to retain customers. Theoretically, this study enriches the literature on ethical consumption by integrating social, political, and religious factors into emerging markets.Originality – This study is among the first to explore the combined effects of animosity and religiosity on brand switching in Indonesia, particularly within the fast-food industry. It highlights boycott intention as a critical mediator, offering novel insights into consumer behavior amid sociopolitical tensions.